Chanarin-Dorfman syndrome - Harshal Ranglani; Pankaj Shukla (Wolters Kluwer Medknow Publications, 2020)
Chanarin-Dorfman syndrome is a rare, autosomal recessive disorder of lipid metabolism, occurring due to mutation of abhydrolase domain containing 5 gene, resulting in the accumulation of triglycerides in the skin, muscles, liver, and other organs. This disorder is clinically characterized by the presence of generalized ichthyosis along with organomegaly and other systemic features, while evidence of vacuolated neutrophils and eosinophils on the peripheral blood smear confirms the diagnosis. We report a 3-year-old girl with Chanarin-Dorfman syndrome to generate awareness about this rare condition.